Sustainable vehicle routing of agro-food grains in the e-commerce industry - Prajapati D.; Chan F.T.S.; Daultani Y.; Pratap S. (My University, 2025)
As a result of rapid industrialisation, rising food demand globally, and, increasing concerns associated with food safety and quality, the implementation of sustainable supply chain concepts is becoming critically important to the agro-food sector. This paper introduces an integrated first-mile pickup and last-mile delivery logistics problem, where agro-food grains are available at multiple farmer’s locations and are in demand by businesses like e-retailers, supermarkets, grocery shops, restaurants, hotels, etc. In addition, this work addresses a sustainable framework for agro-food grains supply chain (AFGSC) in urban and rural areas for e-commerce in developing countries. The proposed optimisation model considers costs related to first-mile pickup, transportation with last-mile delivery, carbon emission tax, inventory holding, vehicle and food damage due to accidents, and penalties on late pickup and delivery. This model also takes environmental and social (due to accidents) sustainability aspects into consideration, along with the economic aspects of sustainability. To solve the large complex practical scenarios by using four nature-inspired algorithms. The obtained results of this study are used to recommend significant managerial insights for implementing AFGSC in the e-commerce industry in considering practical conditions. Moreover, policy implications in terms of economic, social, and environmental aspects of sustainability are also discussed. © 2022 Informa UK Limited, trading as Taylor & Francis Group.